A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species - Sun, Chao; Li, Xu; Zhou, Wei; Li, Fenglian (Zootaxa, 2018)
Species of the genus Garra from the Irrawaddy and Salween River basins in west Yunnan, China are difficult to identify and their taxonomy remains problematic. We conducted a systematic review of the genus using a combination of molecular and morphological approaches to address these issues and describe a new species, G. surgifrons. Phylogenetic analyses indicate that 15 species of Garra do not form a monophyletic group. Garra imberba and G. nujiangensis form a distinct clade that is not sister to the remaining species of Garra. According to the combination of morphological characters of the proboscis and rostrum, Garra from western Yunnan Province can be divided into 4 groups: (1) smooth snout; (2) unilobed proboscis; (3) bi-lobed proboscis; and (4) tri-lobed proboscis. The types of snout shapes in Garra are consistent with the topological structure of the phylogenetic tree. Garra surgifrons can be distinguished from all other congeners occurring in China and Southeast Asia by a combination of the following characters: presence of a transverse lobe and a tri-lobed proboscis; both dorsal and caudal fins without black markings; the proboscis short and broad, a roughly quadrate shape from the dorsal view with a poorly developed and slightly protuberant middle lobe, with the front tip not suspended from the lateral view and the width almost equal to the width of the lateral lobes; the posterior margin of mental adhesive disc extending close to or reaching the vertical through the central line of the eye and never reaching the posterior margin of the eye; two pairs of barbels; 16 circumpeduncular scales; and 32–34 lateral line scales.